Visible‐Light Photoredox‐Catalyzed Cross‐Dehydrogenative Coupling of Tetrahydroisoquinolines with 3‐Fluorooxindoles. Issue 8 (26th July 2019) - Ji, Jian; Chen, Ling‐Yan; Qiu, Zi‐Bin; Ren, Xinfeng; Li, Ya
Abstract: The 3‐fluorooxindole and tetrahydroisoquinoline scaffolds are both important structures because of their associated biological and pharmaceutical activities. Herein, we report a highly diastereoselective synthesis of 3‐fluorooxindoles fully substituted at the 3‐position and containing a tetrahydroisoquinoline fragment, through the visible‐light photoredox‐catalyzed cross‐dehydrogenative coupling of tetrahydroisoquinolines with 3‐fluorooxindoles. The protocol featured a wide substrate scope: N‐alkyl‐, N‐haloalkyl‐, N‐aryl‐, N‐allyl‐, N‐propargyl‐, and NH 3‐fluorooxinloles were all able to be used to form the desired coupling products in up to 92% yield and 99 : 1 anti/syn . Abstract : A highly diastereoselective synthesis of 3‐fluorooxindoles, fully substituted at the 3‐position and containing a tetrahydroisoquinoline fragment, was achieved through the visible‐light photoredox‐catalyzed cross‐dehydrogenative coupling of tetrahydroisoquinolines with 3‐fluorooxindoles.